2010
DOI: 10.1158/0008-5472.can-09-4172
|View full text |Cite|
|
Sign up to set email alerts
|

Correlating Phosphatidylinositol 3-Kinase Inhibitor Efficacy with Signaling Pathway Status: In silico and Biological Evaluations

Abstract: The phosphatidylinositol 3-kinase (PI3K) pathway is frequently activated in human cancers, and several agents targeting this pathway including PI3K/Akt/mammalian target of rapamycin inhibitors have recently entered clinical trials. One question is whether the efficacy of a PI3K pathway inhibitor can be predicted based on the activation status of pathway members. In this study, we examined the mutation, expression, and phosphorylation status of PI3K and Ras pathway members in a panel of 39 pharmacologically wel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
95
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 40 publications
(46 reference statements)
2
95
2
Order By: Relevance
“…As a group, mTOR inhibitor sensitive PIK3CA-mutated breast cancer cell lines did not display increased MAPK pathway activation upon treatment with everolimus or PP242. There is burgeoning evidence to demonstrate that breast cancer cells harbouring PIK3CA mutations are physiologically dependent on this kinase for the activation of RPS6 and survival, whereas PIK3CA wild-type cell lines do not necessarily require PI3K for the activation of the mTOR pathway (Crowder et al, 2009;Dan et al, 2010). These observations suggest a greater dependency of PIK3CA mutant cell lines to the canonical PI3K-AKT-mTOR pathway, which is consistent with our observations.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As a group, mTOR inhibitor sensitive PIK3CA-mutated breast cancer cell lines did not display increased MAPK pathway activation upon treatment with everolimus or PP242. There is burgeoning evidence to demonstrate that breast cancer cells harbouring PIK3CA mutations are physiologically dependent on this kinase for the activation of RPS6 and survival, whereas PIK3CA wild-type cell lines do not necessarily require PI3K for the activation of the mTOR pathway (Crowder et al, 2009;Dan et al, 2010). These observations suggest a greater dependency of PIK3CA mutant cell lines to the canonical PI3K-AKT-mTOR pathway, which is consistent with our observations.…”
Section: Discussionsupporting
confidence: 90%
“…Ctrl, control; MDA, MDA-MB; null, loss of function; wt, wild type; *HER2 amplification. (Dan et al, 2010). On the other hand, PIK3CA mutations were recently reported to predict sensitivity to everolimus in glioblastoma, breast, ovarian, prostate, endometrial and colorectal cancer cells (Di Nicolantonio et al, 2010), to predict response to temsirolimus alone or in combination in patients with advanced cervical, endometrial, ovarian and breast cancer in a phase I clinical trial (Janku et al, 2011), and the PI3K/mTOR dual inhibitor NVP-BEZ235 has been shown to selectively induce cell death in breast cancer cells harbouring PIK3CA mutations (Serra et al, 2008;Brachmann et al, 2009) but not in cells lacking PTEN function (Brachmann et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Identical observations were made for the pan-class I PI3K inhibitor GDC-0941, in an analysis restricted to a panel of 54 breast cancer lines (38). However, another study conducted with different PI3K inhibitors carried out in a panel of 39 lines from 9 different lineages did not show enhanced activity in either PIK3CA or PTEN mutant lines (39). These conflicting data might reflect the fact that, in the latter study, only a small number of lines for each lineage and genetic alteration were analyzed, with a strong imbalance in the representation of each characteristic.…”
Section: Discussionmentioning
confidence: 88%
“…The in vivo anti-angiogenic effect is attributed to its dual inhibition mechanism: inhibition of VEGF secretion by cancer cells and direct inhibition of PI3K in endothelial cells [67] . Oral administration of ZSTK474 indicated favorable in vivo antitumor efficacy on various cancer xenografts at both early and advanced stages, without any obvious toxicity [66][67][68] ( Figure 4C). The expression of phospho-Akt (ser 473) correlates with antitumor efficacy, suggesting this could act as a predictive biomarker [68] .…”
Section: Pi3k a Promising Molecular Target For Cancer Chemo Therapymentioning
confidence: 99%
“…Oral administration of ZSTK474 indicated favorable in vivo antitumor efficacy on various cancer xenografts at both early and advanced stages, without any obvious toxicity [66][67][68] ( Figure 4C). The expression of phospho-Akt (ser 473) correlates with antitumor efficacy, suggesting this could act as a predictive biomarker [68] . Given the favorable preclinical antitumor effect and safety of ZSTK474, the FDA of USA has recently approved the evaluation of this drug candidate in phase I clinical trials.…”
Section: Pi3k a Promising Molecular Target For Cancer Chemo Therapymentioning
confidence: 99%